Analisis Faktor Penyebab Keterlambatan Kereta Api Penumpang di Makassar Pare-Pare - Alfian Mulya Pratama; Tri Rahayu Pujiastuti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to analyze the factors causing delays to passenger trains on the Makassar-Pare-Pare route and to provide recommendations to improve travel timeliness. This research uses a qualitative approach with interview methods and literature study to obtain more in-depth data regarding the factors that influence delays. Based on research results, train delays are caused by several factors, including inadequate infrastructure, irregular track maintenance, extreme weather, as well as technical and operational problems. The results of interviews with officers and passengers revealed that a lack of coordination between field officers and the control center was also one of the main causes. This research suggests the need for improvements in planning departure schedules, increasing coordination between related parties, improving rail infrastructure, and managing passenger density. It is hoped that with these recommendations, train delays can be minimized, provide better comfort for passengers, and improve the quality of train services on the Makassar-Pare-Pare route